An Angiotensinogen Gene Polymorphism (rs5050) Is Associated with the Risk of Coronary Artery Aneurysm in Southern Chinese Children with Kawasaki Disease. (3rd January 2019) - Liu, Yunfeng; Fu, Lanyan; Pi, Lei; Che, Di; Xu, Yufen; Zheng, Hao; Long, Haifeng; Zeng, Lanlan; Huang, Ping; Zhang, Li; Yu, Tao; Gu, Xiaoqiong
Abstract : Background . Kawasaki disease (KD) is an acute vasculitis disease that commonly causes acquired heart disease in children. Coronary artery aneurysm (CAA) is a major complication of KD. However, the pathogenesis of KD remains unclear. The results of a genome-wide association study (GWAS) showed that two functional single-nucleotide polymorphisms (SNPs; rs699A>G and rs5050T>G) in the angiotensinogen (AGT) gene were related to cardiovascular disease susceptibility. The purpose of our study was to estimate the relationship between the two GWAS-identified AGT gene polymorphisms and the risk of CAA in Southern Chinese children with KD. Methods . We genotyped the two AGT gene polymorphisms (rs699A>G and rs5050T>G) in 760 KD cases and 972 healthy controls. We used the odds ratios (ORs) and 95% confidence intervals (CIs) to estimate the degree of the associations. Results . These two AGT gene polymorphisms were not associated with a risk of KD relative to the controls, but after adjusting for sex and age, the carriers of the rs5050G allele with TG/GG vs TT had an adjustedOR = 1.56, 95%C I = 1.01 -2.41, andP = 0.044 relative to the carriers of the rs5050TT genotype. The susceptibility to CAA was more predominant in KD patients younger than 12 months old. Conclusions . Our results indicate that the AGT gene polymorphism rs5050T>G may increase the risk of CAA in children with KD, especially those who are younger than 12 months. These results need to be verified by a validation study with a larger sample size.